In-situ TEM observation on phase formation of TiO2 nanoparticle synthesized by flame method - Jie, H.S.; Park, H.; Kim, K.H.; Ahn, J.P.; Park, J.K. (Materials Science Forum, 2006)
TiO2 nanoparticle was synthesized by the flame method using a metal organic precursor of titanium tetraisopropoxide (TTIP, Ti(OC 3H7)4), which was controlled by varying the ratio and flow rate of gas mixtures consisting of oxygen (oxidizer), methane (fuel) and nitrogen (carrier gas). The morphology and the size distribution of nanoparticles were observed with TEM and FESEM, and the phase evolution was analyzed by XRD measurement using a monochromator. The crystalline phases of TiO2 nanoparticle depended strongly on the temperature distribution in the flame, whereas the morphology was not sensitive. During the flame synthesis of TiO2 nanoparticle, anatase TiO2 nanoparticle was predominantly synthesized at the high flame temperature and rapid flame cooling condition. The low flame temperature and long flame length enabled to form almost rutile TiO2 nanoparticle (>95%). The anatase nanoparticle was formed by a homogeneous nucleation and has finally kept the anatase phase without the phase transformation any more in the flame. However, the rutile TiO2 nanoparticle was not formed directly and homogeneously in flame, and was manufactured by the phase transformation such as amorphous-→anatase-→rutile. It was proved that the rutile phase was nucleated heterogeneously from the amorphous or anatase particles.